Efecto de las actividades humanas sobre la diversidad de mamíferos terrestres en un gradiente altitudinal - Piedra, Lilliana (2000)
The effect of human activity on terrestrial marnmals was studied with footprint counts in Guanacaste, Costa Rica (loo30"N, 85°40'W) in February 1998 (in fifty 2 m2 quadrats). The most cornmon species were Canis latrans, Didelphis marsupialis. Odoicoleus virginianus. Dasyprocta punctata and Tapirus bairdii. No stastically significant association was found between humna activity and marnmal frequency in the footprint counts